Early Female Transgender Identity after Prenatal Exposure to Diethylstilbestrol: Report from a French National Diethylstilbestrol (DES) Cohort - Laura Gaspari; Marie-Odile; Scott Kerlin; Françoise Paris; Charles Sultan (MDPI AG, 2024)
Diagnostic of transsexualism and gender incongruence are terms to describe individuals whose self-identity does not match their sex assignment at birth. A transgender woman is an individual assigned male at birth (AMAB) on the basis of the external or internal genitalia who identifies and lives as a woman. In recent decades, a significant increase in the number of transgender people has been reported. Although, its etiology is unknown, biological, anatomical, genetic, environmental and cultural factors have been suggested to contribute to gender variation. In XY animals, it has been shown that environmental endocrine disruptors, through their anti-androgenic activity, induce a female identity. In this work, we described four XY individuals who were exposed in utero to the xenoestrogen diethylstilbesterol (DES) and were part of the French HHORAGES cohort. They all reported a female transgender identity starting from childhood and adolescence. This high prevalence of male to female transgenderism (1.58%) in our cohort of 253 DES sons suggests that exposure to chemicals with xenoestrogen activity during fetal life may affect the male sex identity and behavior.